Low molecular weight heparin (LMWH) for primary thrombo-prophylaxis in patients with solid malignancies – systematic review and meta-analysis. (September 2014) - Ben-Aharon, Irit; Stemmer, Salomon M.; Leibovici, Leonard; Shpilberg, Ofer; Sulkes, Aaron; Gafter-Gvili, Anat
Abstract Background. Patients receiving chemotherapy for cancer are at increased risk for venous thromboembolism (VTE). We performed a meta-analysis of all randomized controlled trials (RCTs) which evaluated low molecular weight heparin (LMWH) as primary prophylaxis in ambulatory patients with solid malignancies. Methods. A comprehensive search was conducted until October 2013. Primary outcome was symptomatic VTE. Secondary outcomes were pulmonary embolism (PE), any VTE, deep vein thrombosis (DVT), mortality and adverse events. Results. Eleven trials met the inclusion criteria, and evaluated a total of 6942 patients. Primary prophylaxis with LMWH reduced symptomatic VTE (RR 0.46, 95% CI 0.32–0.67) and the rate of PE (RR 0.49, 95% CI 0.29–0.84). In the subgroup analysis of VTE in patients with lung and pancreatic cancers LMWH further reduced VTE [RR 0.42 (95% CI 0.25–0.71); RR 0.31 (95% CI 0.18–0.55), respectively]. Meta-analysis of six trials which reported survival outcomes revealed no statistically significant benefit for LMWH in one-year mortality rates (RR 0.93, 95% CI 0.83–1.04). There was no significant increase in major bleeding events (RR 1.28, 95% CI 0.84–1.95). Conclusions. LMWH reduces the incidence of symptomatic VTE and PE in patients receiving chemotherapy for cancer, with no apparent increase in major bleeding. The benefit is most apparent in pancreatic cancer and also lung cancer. VTE prophylaxis should be considered for these specific populations.